Effects of Milling Parameters on Rheological Behaviours of Silica Nanofluid Prepared by Two-Step Process - Davis, Deepak; Joy, Jil; Singh, Sheela (Asian Journal of Chemistry, 2017)
Nanofluids have garnered the attention of material science and heat transfer fraternity across the world for the reported enhancement of their thermal properties and the amenability for a change of their rheological properties under external influence. Of the various nanofluids that have been studied widely, nano-silica fluids comprise a predominant fraction. The alterations in the morphological characteristics of the nano-silica fluids brought about by mechanical treatment of the samples influence their chemical and rheological behaviours. The present work involves the study of milling parameters on the rheological behaviours of silica particles. The micron size silica is reduced to nano size by ball milling, done by 0-20 h at 300 rpm in Fritsch P5 planetary ball mill. This milled powder will be characterized by XRD and SEM for it crystallite size and morphology. Thus prepared silica on treatment with ethylene glycol and water mixture enhances its dispersion in fluids.